Menyoal tentang Manajemen dalam Perspektif Hadits - Annisaa Siti Zuadah (Gunung Djati Conference Series, 2023)
The purpose of this study is to discuss the hadiths about management. Through content analysis and library research, this research method is qualitative. This research concludes that the Al-Qur'an, sunnah, and ijma' of scholars teach a lot about life discipline. A real illustration of the management that regulates order can be seen in the implementation of prayer, which is considered the most important symbol in Islam. Hajj, fasting and other traditions are excellent forms of management. Of course, the four components (POAC) currently planning, organizing, actuating, and controlling have many verses in the Qur'an and hadith that explain them.